Religiosity Profile and its Correlation with Life Satisfaction among Drug Addicts Undergoing Islamic-Based Inabah Programme in Malaysia - Lua, Pei Lin; Azmi, Hassan; Mokhairi, Makhtar; Julaily Aida, Jusoh (2018)
Lack of religious orientation could lead to moral failing such as drug addiction. Essentially, religion-based approach is becoming a popular method to overcome this problem. The current study intended to describe general religiosity profile and life satisfaction based on socio-demography and to examine the correlation between religiosity profile and life satisfaction among drug addicts undergoing an Islamic-based programme in Kelantan, Malaysia. The Psychological Measure of Islamic Religiousness (PMIR) was administered to 37 participants. Data was analysed using SPSS via. descriptive and non-parametric tests. Findings showed that Islamic faith emerged as the most important religiosity aspect for participants. Across the age groups and educational levels, there was no significant difference in terms of their religiosity profiles and life satisfaction. Global religiousness exhibited strong correlation with life satisfaction (rs = +0.503; p<0.05). s Consequently, this inabah programme seems promising in rehabilitating drug addicts particularly in religious aspects.